Non-immune hydrops fetalis: a case series - Das, Niladri; Malik, Sushma; Gandhi, Prachi; Singh, Vinaya A.; Wade, Poonam (International Journal of Contemporary Pediatrics, 2020)
Hydrops fetalis is a clinical condition characterized by pathological fluid accumulation in soft tissues and serous cavities of the fetus like peritoneal cavity, pleural cavity, pericardial space, and body wall edema. Hydrops fetalis is broadly classified into Immune Hydrops Fetalis (IHF) and Non-Immune Hydrops Fetalis (NIHF). Incidence of immune hydrops fetalis due to Erythroblastosis fetalis secondary to Rh Iso-immunisation has drastically reduced due to widespread use of anti-D immunoglobulin. In the last few decades, the majority of cases are identified as non-immune hydrops. It is important to determine the cause of the hydrops fetalis in order to administer optimal management of the neonate at birth. Despite recent advances the mortality of non-immune hydrops is still high. Authors report here six cases of non-immune hydrops fetalis encountered at our tertiary care hospital over last three years.